Perancangan Bisnis Makanan Anjing "LouLou" Gourmet Bark Cookies - Cherish Catherine Agatha; Marina Wardaya (Jurnal Vicidi, 2017)
This research in order of the making homemade snack or cookies for dogs with brand name “LouLou” Gourmet Bark Cookies to knowing the market respond about this business idea. For this research, writer choose to using qualitative methods by conducting interviews with 10 dog lovers which competent and experienced in taking care of dogs. This interview has a primary focus on dog owners behaviour in terms of feeding and which food materials that dog preferred. The result of this study obtained that dog owners behaviour always give treats, both for training obedience or not, without the exact amount each day, depends with dog owners activity; with various preferred flavour, such as chicken, banana, chicken’s liver, etc, to get its benefits alternately. “LouLou” Gourmet Bark Cookies business idea originated from writer’s baking hobby and experienced, also taking care of dogs since childhood, and then developed by business opportunities and the market problems, which most treats found and sold are import factory product that usually through long processed food that can decreased nutritional value or even contain harmful preservative because of the length of the distribution process before it gets to the customer. Moreover, the treats that sold in market, contains only one flavour in each package so oftenly customer had to buy a lot of packages to get a variety flavours as remembering that dog is a picky eater that tend to choose food. Therefore, “LouLou” Gourmet Bark Cookies business idea are expected to be the solution for market problems.